PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN DAN LOYALITAS NASABAH KREDIT MIKRO PT. BANK BJB BANDAR LAMPUNG - Shafitra Nata Nata (Departemen Manajemen, 2019)
Abstract : This study aims to measure the effect of Marketing Mix (Product, Price, Promotion, Place, Employee, Process, and Physical Evidence) on the Customer Satisfaction of Micro Credit Bank BJB Bandar Lampung Branch and the effect of Customer Satisfaction on Customer Loyalty. Sample in this study is customers of micro credit Bank BJB Bandar Lampung during March 2012 to March 2015, sampling method using Purposive Sampling with samples of 100 respondents. Statistical analysis using multiple linear regression by first using the validity test, reliability test, partial test, and simultaneous test. The results of this study indicate that Marketing Mix (Product, Employee, Process, and Physical Evidence) have a significant effect on Customer Satisfaction, Where the marketing mix which had a dominant influence is the process and followed by the product. The relationship of consumer satisfaction with loyalty of a positive impact on customer loyalty PT. Bank BJB Bandar Lampung micro credit customers.Keywords: Marketing Mix, Customer Satisfaction, and Customer Loyalty.